2021
DOI: 10.1002/celc.202100424
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Charge Accumulation and Oxygen Reduction Catalysis in Nanostructured TiO2 Electrodes Functionalized with a Molecular Catalyst

Abstract: The catalytic reduction of O 2 by a manganese(III) porphyrin immobilized in a nanostructured semiconductive transparent TiO 2 electrode is here investigated by UV-Vis spectroelectrochemistry in an aqueous buffered medium. Analysis of the operando spectroelectrochemical data, collected for both the immobilized catalyst and the TiO 2 matrix, demonstrates the coexistence of two faradaic electrochemical processes, namely (i) irreversible interfacial electron transfer from TiO 2 to the immobilized porphyrin trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…[26] In our group, we also revealed the faradaic interplay between the reversible insertion of protons in TiO 2 and the catalytic reduction of O 2 via an iron porphyrin immobilized within the mesoporous structure of a TiO 2 electrode. [27] More recently, the Augustyn and Mpourmpakis/McKone groups have both suggested that protons inserted into WO 3 govern the reactivity toward the hydrogen evolution reaction. [28,29] All these elements reinforce the idea that there is a crucial need to elucidate the key factors governing PICET reactions, and more specifically in aqueous unbuffered media.…”
Section: Introductionmentioning
confidence: 99%
“…[26] In our group, we also revealed the faradaic interplay between the reversible insertion of protons in TiO 2 and the catalytic reduction of O 2 via an iron porphyrin immobilized within the mesoporous structure of a TiO 2 electrode. [27] More recently, the Augustyn and Mpourmpakis/McKone groups have both suggested that protons inserted into WO 3 govern the reactivity toward the hydrogen evolution reaction. [28,29] All these elements reinforce the idea that there is a crucial need to elucidate the key factors governing PICET reactions, and more specifically in aqueous unbuffered media.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mesoporous TiO 2 electrodes or other high-surface-area assemblies containing TiO 2 often appear to be stable photocathodes and supports for tethered molecular catalysts, despite the fact that the TiO 2 is likely being reduced during catalysis. Indeed, Balland et al recently demonstrated that a high-surface-area assembly consisting of a TiO 2 -tethered molecular O 2 reduction catalyst undergoes both catalysis and proton-coupled reduction of the TiO 2 . In this case, the reduced TiOOH is not a source of instability but rather a charge storage reservoir that facilitates catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…This need for e − /H + accumulation for TiO 2 to act as an electrode has long been known. 34,102,103 Modeling the CV response, however, is challenging, and the TiO 2 /Si electrode is even more complex. The concentrations of electrons and holes at the Si surface and the potential drop within the Si vary with applied potential and other factors.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations